A nitrogen-rich, azaindole-based microporous organic network: synergistic effect of local dipole–π and dipole–quadrupole interactions on carbon dioxide uptake. Issue 37 (12th September 2016) - Chang, Guanjun; Yang, Li; Yang, Junxiao; Huang, Yawen; Cao, Ke; Ma, Jiajun; Wang, Dapeng
Abstract : A new type of microporous organic polymer with azaindole units (N-PEINK) has been designed. Abstract : A new type of microporous organic polymer with azaindole units (N-PEINK) has been designed. The resulting N-PEINK exhibits good chemical and thermal stability with a decomposition temperature of 550 °C. Taking advantage of the synergistic effect of local dipole–π and dipole–quadrupole interactions between azaindole and carbon dioxide (CO2 ), the CO2 uptake capacity of the polymer reaches 20.8 wt% (1.0 bar, 273 K) with high selectivities (CO2 /N2 = 97, CO2 /CH4 = 18), making the polymer a promising microporous material for application in CO2 separation and capture. Furthermore, the azaindole-based microporous organic polymer also exhibits a high hydrogen storage (2.67 wt%) at 1.0 bar and 77 K. For comparison, the microporous organic polymer with indole units (PEINK) was also prepared.